Usability Evaluation of a Web-Based e-KMS for Toddler Nutritional Status Monitoring Using the System Usability Scale (SUS) - Niyalatul Muna; Indah Muflihatin; Ida Nurmawati; Demiawan Rachmatta Putro Mudiono; Andri Permana Wicaksono (International Journal of Healthcare and Information Technology, 2026)
A nutritional status assessment system is an electronic health information system that records toddler growth based on age-specific weight and height measurements. Parents may not always maintain appropriate scheduling or regular visits for periodic monitoring at healthcare facilities. This study presents a usability evaluation of a web-based nutritional monitoring system that implements an Electronic Growth Monitoring Card (e-KMS). Users interact with the system through a user interface (UI) and user experience (UX) designed to support effective interaction. The main contribution of this study is the empirical validation of the usability level of a web-based e-KMS in a healthcare context using the System Usability Scale (SUS). The evaluation involved 20 respondents, consisting of parent representatives and daycare teachers or administrators as e-KMS users, and employed 10 SUS statements measured on a five-point Likert scale. The SUS analysis yielded a score of 77.78, indicating a good and acceptable level of usability. These findings demonstrate that the developed e-KMS is suitable for supporting digital-based monitoring of toddler nutritional status in healthcare services.